(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
This essay asks for the impact of grammar as enframing for the perception, interpretation and praxis of peace. It reflects the urge for a subject in all grammars of European origin since antiquity and discusses the colonizing consequences of the metaphysical peace as a singular in its transcendental context. This noun contrasts with action- and proceeding-oriented understandings of peace in many non-European languages. Such post-modern insight called the academic discipline of peace studies decades ago for the understanding of peaces as plural. This essay goes one step further and proposes to peace as a verb also for European grammars. It asks for the possibly de-colonizing and enlightening consequences of such an immanent notion in the still transcendental modern context.